DORMANSI PADA BIJI KEDAWUNG (Parkia javanica (Lam.) Merr.): PENGARUH SKARIFIKASI DAN APLIKASI STIMULAN KIMIAWI TERHADAP PERKECAMBAHAN BIJI - Kristiati, Elly; Putri, Winda Utami (Center for Plant Conservation Bogor Botanic Garden, Indonesian Institute of Sciences, 2008)
A study on seed germination of Kedawung was conducted in the Bogor Botanic Garden using seeds collected from living plant collection of the Purwodadi Botanic Garden. The purpose of the study was to reveal dormancy characteristics of the seed and to search for the effective method of enhancing seed germination of the species. Overall, seventeen treatments of scarification and application of chemical stimulants were tested. The result showed that scarification treatment is critical for promoting Kedawung seed germination. Nicking of the seed testa provided the best result with 80 % seed germination. Soaking the seeds in boiling water also helped the seed to germinate up to 62 %, especially when the time of soaking was appropriate. Meanwhile, the effect of chemical stimulants, i.e. KNO3 and GA3, was evident only if the application was preceded by a scarification treatment. Seed germination was enhanced with the application of either 500 ppm KNO3 or 1500 ppm GA3. These results suggest that the majority of kedawung seeds have physical dormancy (PY), but some may also have physiological dormancy (PD), and only a very little portion of them are evidently non-dormant seeds.